Evolutional and clinical implications of the epigenetic regulation of protein glycosylation - Horvat, Tomislav (Springer-Verlag, 2011)
Protein N glycosylation is an ancient posttranslational modification that enriches protein structure and function. The addition of one or more complex oligosaccharides (glycans) to the backbones of the majority of eukaryotic proteins makes the glycoproteome several orders of magnitude more complex than the proteome itself. Contrary to polypeptides, which are defined by a sequence of nucleotides in the corresponding genes, glycan parts of glycoproteins are synthesized by the activity of hundreds of factors forming a complex dynamic network. These are defined by both the DNA sequence and the modes of regulating gene expression levels of all the genes involved in N glycosylation. Due to the absence of a direct genetic template, glycans are particularly versatile and apparently a large part of human variation derives from differences in protein glycosylation. However, composition of the individual glycome is temporally very constant, indicating the existence of stable regulatory mechanisms. Studies of epigenetic mechanisms involved in protein glycosylation are still scarce, but the results suggest that they might not only be important for the maintenance of a particular glycophenotype through cell division and potentially across generations but also for the introduction of changes during the adaptive evolution.